Baseline Soil and Water Quality for Sustainable Agriculture–Aquaculture Systems in Keerom, Papua, Indonesia - WOROROMI, JONATHAN K.; PURNAMASARI, VITA; WAMBRAUW, DANIEL Z.K.; AGAMAWAN, LALU P.I.; SIMBIAK, IRJA T.; RAMANDEY, EUNICHE R.P.F; KEILUHU, HENDERINA J.; SUYONO, IGN. JOKO (Jurnal Biologi Papua, 2025)
Tropical frontier regions such as Keerom Regency in Papua, Indonesia, face increasing pressure to expand food production under the National Strategic Projects (PSN) for food security. However, the absence of baseline data on soil fertility and water quality constrains the design of sustainable management practices. This study evaluated the temporal variation in soil chemical properties and aquaculture water quality to establish scientific benchmarks for site-specific interventions. Soil samples from chilli pepper (Capsicum annuum) farms were collected across resting, early growth, pre-harvest, and intercropping stages, while water samples from catfish (Clarias spp.) ponds were obtained during larval, grow-out, and harvest phases. Soil pH declined from 6.5 to 4.4, accompanied by reductions in total N, P, and K and a gradual rise in EC, indicating nutrient depletion and increasing acidity. In aquaculture ponds, DO levels decreased while Ammonium and nitrite accumulated during intensive feeding, suggesting excessive organic loading and incomplete nitrification. These results reveal critical limitations in both systems that reduce productivity and environmental resilience. The findings provide essential baseline data for nutrient management, fertilizer optimization, and water-quality control, forming a scientific foundation for future integrated agriculture–aquaculture (IAA) development to strengthen regional and national food-security initiatives in Papua.